KESANTUNAN BERBAHASA DALAM TEKS ALAT PERAGA KAMPANYE PILKADA BANTEN 2024 UNTUK PEMBELAJARAN BAHASA IKLAN DI SMP - Afdal Eki Pratama; Dase Erwin Juansah; Dodi Firmansyah (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study discusses the use of politeness in the 2024 Banten Regional Election campaign materials found on billboards and pamphlets, with the aim of describing the realisation of politeness maxims based on Geoffrey Leech's (1983) theory and implementing them in advertising language learning at the junior high school level. The research method used was qualitative descriptive with data collection techniques through documentation, coding, and discourse analysis. The research data consisted of 36 campaign texts analysed based on six maxims of politeness. The results showed that there were 36 data points for all maxims of politeness, namely 10 maxims of sympathy, 6 of praise/appreciation, 11 of agreement, 2 of generosity, 4 of humility, and 3 of wisdom/prudence, identified in the campaign texts. Each maxim serves to reinforce the candidate's positive image while influencing public opinion in a polite manner. The findings of this study can be used as teaching material for advertising language in junior high schools because they provide concrete examples of the application of polite and contextually appropriate persuasive language. This study contributes to enriching pragmatic studies and supports the development of students' advertising text analysis and production skills.